2020
DOI: 10.51594/estj.v1i1.36
|View full text |Cite
|
Sign up to set email alerts
|

A Discrete Event Simulation (Des) Based Approach to Maximize the Patient Throughput in Outpatient Clinic

Abstract: The healthcare system is a complex system which exhibits conditions of uncertainty, ambiguity emergence that incurs incoming patient congestion. Discrete event simulation (FlexSim) is considered as a viable decision support tool in analyzing a system for improvement. Using a data-driven discrete event simulation approach, this paper portrays a comprehensive analysis to maximize the number of patients in an on-campus clinic, located at Mississippi State University. The outcome of the analysis of current system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…The transition probabilities are assumed to depend on the current state, and the time spent in each step is considered to depend on the present and following conditions [ 45 , 46 ]. Many researchers use Markovian methods to investigate service scheduling research, such as for ambulance unloading delays, a Markovian queueing model was used [ 47 , 48 ]. Another analysis that used the Markovian model to estimate patient services was the basic Markovian model's waiting time in a hospital using order statistics [ 49 , 50 ].…”
Section: Results and Analysismentioning
confidence: 99%
“…The transition probabilities are assumed to depend on the current state, and the time spent in each step is considered to depend on the present and following conditions [ 45 , 46 ]. Many researchers use Markovian methods to investigate service scheduling research, such as for ambulance unloading delays, a Markovian queueing model was used [ 47 , 48 ]. Another analysis that used the Markovian model to estimate patient services was the basic Markovian model's waiting time in a hospital using order statistics [ 49 , 50 ].…”
Section: Results and Analysismentioning
confidence: 99%
“…For centuries, patient waiting times (WT) have been a persistent issue in the healthcare industry. 13-18 Long patient WT can be caused by many factors and would affect the quality of care in hospitals. 19 Arneill and Devlin 17 concluded that the physical environment of the waiting room has an impact on the overall quality of care.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Practitioners are left with no choice but to deal with these escalating characteristics and challenges. Thus, dealing with the challenges inherent in modern systems necessitates the adoption of a more 'systemic' approach to better discern and govern problems [11][12][13][14][15][16][17][18]. One systemic approach is the use of systems thinking and a systems theory paradigm.…”
Section: Introductionmentioning
confidence: 99%